SYNTHESIS AND CHARACTERIZATION OF CELLULOSE STEARATE ESTER FROM BACTERIAL CELLULOSE AND STEARIC ACID ENZYMATICALLY USING IMMOBILIZED LIPASE - Suci Amaliyah (Molekul, 2016)
The aims of this study were to determine the optimum conditions of enzymatic esterification between stearic acid with bacterial cellulose using immobilized lipase and to characterize the obtained ester. The optimum condition was observed by the effects of time and mass ratio of cellulose: stearic acid towards degree of esterification. The esterification reaction carried out in a heterogeneous system using n-butanol as solvent at 50 °C. The effect of reaction time on esterification degree is done by variating incubation time for 6, 12, 18, 24 and 30 hours. The influence of the mass ratio of cellulose: stearic acid to the esterification degree was carried out by variating 1: 1, 1: 2, 1: 3, 1: 4, 1: 5 and 1: 6. Products characterization consist of functional group analysis by Fourier Transform Infra Red (FTIR), determining degree of substitution (DS) by saponification, swelling index by gravimetric method, and cristallinity by X-Ray Diffraction (XRD). The results showed that condition of esterification was optimum in 18 hours of reaction with mass ratio 1:5. The success of esterification was confirmed by FTIR spectrum that showed ester carbonyl peak at 1718.46 cm-1 . DS of  cellulose stearate ester was 0.35. The swelling and crystallinity index of cellulose stearate was smaller than bacterial cellulose.